Clinical Observation of Posterior-Chamber Phakic Implantable Collamer Lens V4c Implantation in Myopic Patients with Shallow Anterior Chamber Depth: A Retrospective, Consecutive Observational Study - Juan Yuan; Shuang Wu; Zongli Hu; Chunlin Chen; Shiyang Ye; Jian Ye (Journal of Ophthalmology)
Purpose. The reference range for the preoperative anterior chamber angle width for ICL surgery is unclear. Our objective was to assess the clinical effect and the range of anterior chamber angle width of posterior-chamber implantable collamer lens V4c (ICL V4c) implantation in patients with anterior chamber depth (ACD) < 2.8 mm. Methods. Patients who underwent ICL V4c implantation with shallow ACD were included in this retrospective study. The patients’ uncorrected and corrected distance visual acuity, angle of trabecular-iris (TIA), angle-opening distance (AOD500), trabecular-iris space area (TISA500), corneal endothelial cell density, vault, retinal nerve fiber layer thickness, intraocular pressure, visual field, and complications were analyzed. Results. Forty-one patients (68 eyes) completed at least 12 months of follow-up (median follow-up, 30 months). The effectiveness and safety indices were 1.09 ± 0.13 and 1.04 ± 0.21, respectively. The preoperative TIA values on the nasal and temporal sides were 39.78 ± 7.68 degree (range, 25.8-65.1 degree) and 41.54 ± 8.03 degree (range, 28.5-63.00 degree). Forty-seven eyes had uncorrected distance visual acuity ≥1.0, and 55 had corrected distance visual acuity ≥1.0 at the last follow-up visit. The TIA, AOD500, and TISA500 on the nasal and temporal sides were significantly reduced compared to those before surgery (all P<0.01); no eye had an angle closure or elevated intraocular pressure. The ICL V4c vault was 290.88 ± 153.36 μm (range, 60.0-880.0 μm). No severe complications occurred in any patient. Conclusions. In patients with myopia with shallow ACD (2.55-2.79 mm), a preoperative TIA >25.8° is safe and effective for a relatively long time after surgery; however, an extended long-term close follow-up is needed.